PROFESSIONAL ACCOUNTING EXAMINATIONS IN GREAT BRITAIN. - Weinwurm, Ernest H. (The Accounting Review, 1957)
Publication of the long-awaited report on standards of education and experience for CPAs is bound to lead to a review of the present system of professional accounting examinations in the United States. Since the accounting profession in this country is a direct descendent of the earlier development in Great Britain, a brief description of the system of examination in that country should make a useful contribution at this time. There are seven organizations of professional accountants in Great Britain which conduct their own professional examinations as a pre-requisite for admission to membership. The peculiar feature of the Institutes is their rigid reliance on the apprenticeship system. A candidate for membership must serve for five years as an articled clerk with a member who is called the principal. In the past it was customary for principals to charge a premium for the apprenticeship. The Association of Certified and Corporate Accountants was formed through the merger of a number of smaller accounting groups.